The Number of Quranic Verses: Historical Opinions, Differences, and an Analytical Study of the Correct View - Talat Mehmood; Dr Farhadullah* (Journal of Religion and Society, 2025)
The present article examines the scholarly discourse on the number of verses in the Qur’an (ʾĀyāt al-Qurʾān) and addresses common misconceptions surrounding this issue. Linguistically, the word āyah means “sign” or “mark,” while in Qur’anic usage it refers to a passage upon which pausing is considered appropriate. Classical sources, including al-Itqān of al-Suyūṭī and al-Burhān of al-Zarkashī, report consensus among Muslim scholars that the Qur’an contains more than six thousand verses, with variations depending on the method of counting. Six major traditions of verse enumeration are identified: Madanī (early and late), Makki, Shāmī, Baṣrī, and Kūfī. Among these, the Kūfī enumeration recorded as 6,236 verses and attributed to Imām ʿAlī (RA) has been widely accepted and remains the standard in the muṣḥafs used by the Muslim world today. The article further explores narrations attributing higher counts, such as 6,616 (to Ibn ʿAbbās) and the commonly cited 6,666, noting that these are either weak in transmission or the result of thematic approximations (e.g., verses of promise, warning, command, prohibition, etc.). The study emphasizes that the differences in enumeration arise not from textual discrepancies but from variations in considering whether certain phrases constitute independent verses or continuations. It concludes that all Muslims unanimously affirm the completeness and preservation of the Qur’an from al-Ḥamd (Sūrat al-Fātiḥah) to al-Nās (Sūrat al-Nās) without addition or omission. The diversity in counting methods reflects historical approaches to recitation and teaching, rather than any difference in the Qur’anic text itself. Keywords: Qur’anic verses, Verse enumeration,ʿAdd al-Āy, Kūfī count, ʿUlūm al-Qur’ān (Qur’anic sciences), The 6666 verses issue, Preservation of the Qur’an